Humor me / [videorecording (DVD)]. - Hoffman, Sam; Hoffman, Sam; Hoffman, Sam; Clement, Jemaine; Gould, Elliott; Michaelson, Ingrid (Shout! Factory, 2018)
After his wife leaves him, a struggling New York playwright moves in with his father in his New Jersey retirement community, and is soon enlisted to help with a senior citizen theater troupe staging a musical.